Commodity risk assessment of Salix caprea and Salix cinerea plants from the UK - EFSA Panel on Plant Health (PLH); Antonio Vicent Civera; Paula Baptista; Anna Berlin; Elisavet Chatzivassiliou; Jaime Cubero; Nik Cunniffe; Eduardo de laPeña; Nicolas Desneux; Francesco Di Serio; Anna Filipiak; Beata Hasiów‐Jaroszewska; et al. (EFSA Journal, 2025)
Abstract The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as ‘High risk plants, plant products and other objects’. This Scientific Opinion covers plant health risks posed by plants of Salix caprea and Salix cinerea imported from the United Kingdom (UK) as: (a) bundles of 1‐ to 2‐year old cuttings/graftwood, (b) 1‐ to 7‐year‐old bare root plants, (c) 1‐ to 2‐year‐old cell grown plants and (d) 2‐ to 15‐year‐old plants in pots, taking into account the available scientific information, including the technical information provided by the UK. All pests associated with the commodities were evaluated against specific criteria for their relevance for this opinion. Two EU protected zone quarantine pests, i.e. Bemisia tabaci (European populations) and Entoleuca mammata, and one EU quarantine pest, i.e. Phytophthora ramorum (non‐EU isolates), fulfilled all relevant criteria and were selected for further evaluation. For the selected pests, the risk mitigation measures described in the technical dossier from the UK were evaluated. Expert judgements were given on the likelihood of pest freedom taking into consideration the risk mitigation measures acting on the pests, including uncertainties associated with the assessment. The age of the plants was considered, reasoning that older trees are more likely to be infested mainly due to longer exposure time and larger size. The degree of pest freedom varies between the pests evaluated, with P. ramorum being the pest most frequently expected on the imported plants. The Expert Knowledge Elicitation (EKE) indicated with 95% certainty that between 9738 and 10,000 rooted S. caprea and S. cinerea plants in pots (2 to 15‐year‐old) per 10,000 will be free from P. ramorum.